1999
DOI: 10.1007/s004170050268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical dorzolamide on optic nerve head blood flow

Abstract: The results showed the expected drop in IOP. However, capillary optic nerve head blood flow, measured by two different techniques, did not change during therapy. This may be due to the effective autoregulation in human optic nerve head circulation, which seems not to be affected by dorzolamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 19 publications
1
24
1
2
Order By: Relevance
“…31,32 In NTG patients, dorzolamide significantly reduced arteriovenous passage (AVP) time in the superior temporal retina and improved contrast sensitivity at both 3 and 6 cycles/degree. 33,34 Other studies on retrobulbar vessels 35 and at the retinal level 36 did not find any significant effect of dorzolamide instillation on OBF in healthy subjects. The fixed combination of timolol and dorzolamide (D/T) has been proven to be as effective in lowering IOP as the concomitant use of the two molecules and more effective than either in monotherapy.…”
Section: Introductionmentioning
confidence: 84%
“…31,32 In NTG patients, dorzolamide significantly reduced arteriovenous passage (AVP) time in the superior temporal retina and improved contrast sensitivity at both 3 and 6 cycles/degree. 33,34 Other studies on retrobulbar vessels 35 and at the retinal level 36 did not find any significant effect of dorzolamide instillation on OBF in healthy subjects. The fixed combination of timolol and dorzolamide (D/T) has been proven to be as effective in lowering IOP as the concomitant use of the two molecules and more effective than either in monotherapy.…”
Section: Introductionmentioning
confidence: 84%
“…In contrast, carteolol, betaxolol and nipradilol reportedly increased ONH blood flow in humans (Tamaki et al, 1997a(Tamaki et al, , 1997bTamaki et al, 1999;Mizuno et al, 2002). It was reported that dorzolamide, a topical CAI, had no significant effect on ONH blood flow in healthy subjects but increased ONH blood flow in glaucoma patients (Pillunat et al, 1999;Fuchsjäger-Mayrl et al, 2005;Rolle et al, 2008). To the best of our knowledge, there have been few reports on the effect of brinzolamide, another topical CAI, on ONH blood flow in humans (Iester et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] However, not all studies have reported a positive outcome. [21][22][23] Relatively few studies have evaluated the effect of topical brinzolamide upon OBF in glaucoma patients.…”
Section: Introductionmentioning
confidence: 99%